Children's cognitive responses to constructive television news. (April 2019) - Kleemans, Mariska; Dohmen, Roos; Schlindwein, Luise F; Tamboer, Sanne L; de Leeuw, Rebecca NH; Buijzen, Moniek
Given the importance of news in preparing children for their role as active citizens in society, insight into how negative news can be delivered to children most optimally is warranted. In this regard, this study examined the usefulness of constructive news reporting (i.e. solution-based news stories including positive emotions). An experiment ( N = 281 children, 9–13 years old) was conducted to investigate how constructive, compared to nonconstructive, news reporting affected recall of television news, and whether negative emotions elicited by this news mediated this relation. Analyses of covariance revealed that children in the constructive condition displayed a lower recall of the general information about the event. In contrast, their recall of constructive stories was better compared to the recall of comparable, but nonconstructive, stories by children in the nonconstructive condition. Fear and sadness elicited by the news did not mediate the relation between news reporting style and recall. Instead, constructive reporting directly induced smaller increases in fear and sadness than nonconstructive reporting. To conclude, the negative aspects of the news event were less prominently available in memory of children exposed to constructive news.